2015
DOI: 10.1186/s12863-015-0199-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and confirming quantitative trait loci associated with heat tolerance at flowering stage in different rice populations

Abstract: BackgroundClimate change is affecting rice production in many countries. Developing new rice varieties with heat tolerance is an essential way to sustain rice production in future global warming. We have previously reported four quantitative trait loci (QTLs) responsible for rice spikelet fertility under high temperature at flowering stage from an IR64/N22 population. To further explore additional QTL from other varieties, two bi-parental F2 populations and one three-way F2 population derived from heat toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 31 publications
5
114
0
1
Order By: Relevance
“…The heat tolerance of the nIL carrying qHTSF4.1 was increased consistently in all of the backcross populations. In BC 3 F 3 , spikelet fertility of plants with qHTSF4.1 (34.7 ± 14.2%) was significantly higher than in those without the QTL (22.5 ± 7.9%) and recurrent parent IR64 Ye et al (2015a) identified and used in our breeding programs. A thermotolerance gene (TT1) in African rice (O. glaberrima) variety CG14 was cloned .…”
Section: Genetic Analyses For Hiss At Floweringmentioning
confidence: 95%
See 2 more Smart Citations
“…The heat tolerance of the nIL carrying qHTSF4.1 was increased consistently in all of the backcross populations. In BC 3 F 3 , spikelet fertility of plants with qHTSF4.1 (34.7 ± 14.2%) was significantly higher than in those without the QTL (22.5 ± 7.9%) and recurrent parent IR64 Ye et al (2015a) identified and used in our breeding programs. A thermotolerance gene (TT1) in African rice (O. glaberrima) variety CG14 was cloned .…”
Section: Genetic Analyses For Hiss At Floweringmentioning
confidence: 95%
“…Some of the QTLs identified in different populations are overlapped or closely linked (Table 1). Among the identified QTLs, a QTL for spikelet fertility under high temperature, qHTSF4.1 from n22, was identified in different genetic backgrounds in different studies (Jagadish et al, 2010;Xiao et al, 2011;Ye et al, 2012Ye et al, , 2015a. To fine map and validate the effect of heat tolerance QTL qHTSF4.1, PCR-based SnP markers were developed and used to genotype BC 2 F 2 , BC 3 F 2 , BC 3 F 3 , and BC 5 F 2 populations from the cross combination of IR64/n22.…”
Section: Genetic Analyses For Hiss At Floweringmentioning
confidence: 99%
See 1 more Smart Citation
“…The second QTL qSTIY5.1/qSSIY5.1, which has been previously reported was established in chromosome 5 at a narrower 331 kbp region compared to 23Mb in the original study. Although several QTLs control heat tolerance at flowering stage, QTL qHTSF4.1 can be an importance source for HTS tolerance since it was found consistently across genetic backgrounds of RILs involving crosses of IR64, N22, Giza178 and Milyang23 (Ye et al, 2015). Figure 6A shows the various published QTLs associated with heat tolerance at flowering stage in different rice genotypes including Azucena, Bala, Toyonishiki, T226, T219 and IR64 (Ye et al, 2012).…”
Section: Mapping Of Genetic Loci (Qtl) and Genome-wide Association Stmentioning
confidence: 99%
“…The identified QTLs can be used for marker assisted breeding program in wheat for improved heat tolerance. In rice, QTL qHTSF4.1 showing consistent performance across different genetic backgrounds has been identified which could be used as an important source for enhancing heat tolerance in rice at flowering stage [130].…”
Section: Heat Tolerant Related Morpho-physiological Traitsmentioning
confidence: 99%